Phytoplankton communities as indicator of trophic state in some habitats of Batanghari River system in Sumatera Island, Indonesia - Sulastri Sulastri; Lumbantoruan Reliana; Sudarso Jojok; Sukamto Tedjo (BIO Web of Conferences)
Deforestation, land use change, expansion of agriculture, which may have an impact water quality in Batanghari River habitat. Phytoplankton composition, abundance, diversity and functional group were observed to know the trophic and ecological status of Batanghari River habitats. Phytoplankton samples and water quality were collected in 2022 at eight sampling sites. The result showed that phytoplankton abundance ranges from 85 to 3264 individuals L-1 indicating medium to low productivity. Phytoplankton community included seven divisions as Bacillariophyta, Chrysophyta, Chlorophyta, Cyanophyta, Pyrrophyta, Euglenophyta and Cryptophyta. Euglenophyta, Pyrrophyta and Chlorophyta are dominant group contributing 63.3 %, 63.58%, and 82.98 % to Batang Tebo, Lake Teluk and Lake Toman station respectively. A high total number of species (58 to 60) was recorded in Lake Sigombak and Lake Teluk. Diversity index (H’), showed most habitats in Batanghari River were classified as moderate ecological stress. A higher diversity index (2.645), species richness index (4.141), similarity index (0.763), low conductivity, low TDS and high percentage of PFGs NA indicating healthier and mesotrophic waters was recorded in Lake Sigombak. Low of index diversity (1.658 to 1.715), index species richness (1.387 to 2.181), index similarity (0.488 to 0.661) and pH (1.34 to 2.55) were found in peat swamp.